An Overview of Theoretical Models of Exchange Bias Mechanism (International Journal of Engineering and Computer Science, 2017)
The research activities on the phenomenon of exchange bias (EB) has recently promulgated due to its versatile use in magnetic sensors and as stabilizers in magnetic reading heads. Since the discovery of EB in 1956, the attention on this matter was limited until such applications related to giant magnetoresistance were developed during late 90’s. This study primarily focuses on the understanding of the phenomenon of EB by reviewing and critically discussing the various theoretical models developed and refined over the years. Relevant characteristics of the bias, coercivity fields, the sensitivity and dependence of the fields to interface structure and quality, long-term stability for the magnitude of the bias field and the orientation of the ferromagnet are discussed in the light of these theoretical models.